Adenosine kinase is a key determinant for the anti‐HCV activity of ribavirin. Issue 4 (19th August 2013) - Mori, Kyoko; Hiraoka, Osamu; Ikeda, Masanori; Ariumi, Yasuo; Hiramoto, Akiko; Wataya, Yusuke; Kato, Nobuyuki
<x xml:space="preserve">Abstract</x> Ribavirin (RBV) is often used in conjunction with interferon‐based therapy for patients with chronic hepatitis C. There is a drastic difference in the anti–hepatitis C virus (HCV) activity of RBV between the HuH‐7‐derived assay system, OR6, possessing the RBV‐resistant phenotype (50% effective concentration [EC50]: >100 µM) and the recently discovered Li23‐derived assay system, ORL8, possessing the RBV‐sensitive phenotype (EC50: 8 µM; clinically achievable concentration). This is because the anti‐HCV activity of RBV was mediated by the inhibition of inosine monophosphate dehydrogenase in RBV‐sensitive ORL8 cells harboring HCV RNA. By means of comparative analyses using RBV‐resistant OR6 cells and RBV‐sensitive ORL8 cells, we tried to identify host factor(s) determining the anti‐HCV activity of RBV. We found that the expression of adenosine kinase (ADK) in ORL8 cells was significantly higher than that in RBV‐resistant OR6 cells harboring HCV RNA. Ectopic ADK expression in OR6 cells converted them from an RBV‐resistant to an RBV‐sensitive phenotype, and inhibition of ADK abolished the activity of RBV. We showed that the differential ADK expression between ORL8 and OR6 cells was not the result of genetic polymorphisms in the ADK gene promoter region and was not mediated by a microRNA control mechanism. We found that the 5' untranslated region (UTR) of ADK messenger RNA in ORL8 cells was longer than that in OR6 cells, and that only a long 5' UTR possessed internal ribosome entry site (IRES) activity. Finally, we demonstrated that the long 5' UTR functioned as an IRES in primary human hepatocytes. Conclusion: These results indicate that ADK acts as a determinant for the activity of RBV and provide new insight into the molecular mechanism underlying differential drug sensitivity. (Hepatology 2013;58:1236–1244)